Report on the Creation of the "Sense of Vision" Application Using Android-Based Augmented Reality Technology - Siska Dyah Setiyawati; Muhammad Falah; Tesyalonika Dhevina Pramudhita; Rizdha Buwana Hadi; Yulaikha Yulaikha (Journal of Software Engineering, Information and Communication Technology (SEICT), 2021)
Making the "Sense of Sight" application using Android-based augmented reality technology is  an innovation that was created as a means to help elementary school children understand  natural sciences class IV (four) theme 5 material on the sense of sight more effectively and  interactively. When viewed in terms of the theoretical benefits of research, this research was  created in order to provide a new concept in the world of education and can be used as  reference material for further similar research. Then, the practical benefit of this research is  that researchers gain knowledge to apply a technology in learning in the form of an  application and can be used by students so that learning will be more effective and enjoyable.  The results of this study are in the form of visual sensory application products using Android based Augmented Reality technology, which teachers can use as one of the learning media on  theme 5, namely the sense of sight